Design and research of an online continuous monitoring instrument for Iodine-129 in reprocessing facilities - Yang Kang; Cao Ya-Bin; Zhang Wei; Wang Xin (International Journal of Advanced Nuclear Reactor Design and Technology, 2025)
This paper presents the design of an I-129 online continuous monitor based on the I-129 measurement scenario in the reprocessing plant, the characteristics of the NaI(Tl) crystal, the results of MCNP simulation calculations, and the saturation sampling time of the iodine cartridge. This design can effectively mitigate the interference from a large number of Kr-85 nuclides during the I-129 measurement process and satisfy engineering measurement requirements. By correcting the detection efficiency of the I-129 online continuous monitor and integrating this with the instrument design, we derive the calculation formula for I-129 activity concentration, providing theoretical support for instrument program development.